ANALISIS PERFORMANSI JARINGAN 4G LTE DI GEDUNG ITL FT UNP KAMPUS AIR TAWAR BARAT - Yerry Rahmaddian; Yasdinul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Analysis of network performance is needed in the ITL building which is a new building in the Padang State University area. The purpose of this study was to determine the performance of the 4G LTE network in the ITL by using the G-Net Track Pro application.  This research is a descriptive research that analyzes the results of the drive test based on RSRP, RSRO & SNR parameters. Data analysis results show: (1) The average RSRP value is -86.65 dBm (Good), the RSRQ average value is -12.70 dB (Medium) and the average SNR value is 2.73 dB (Medium) (2) The best parameter value of RSRP Floor 4 is point B -78.3 B), RSRQ (Floor 3 point B is -11.85 dB) and  SNR (Floor 4 point B is 5.14 dB) (3) from all data, the percentage of categories around 6% Excellent, 17% Good, 56% Medium, 18% Poor and 3% of data in the 3G network category are obtained.  The data suggests that the performance in this building is  quite well, but it is not maximal and the signal strength received is not evenly distributed . network quality improvement is needed in order to improve performance for maximum & even signal strength throughout the building.  Keywords: LTE, Drive Test, RSRP, RSRQ, SNR